Assessing the impact of the Academic Quality Improvement Project on the organizational climate of a comprehensive community college: a case study approach - Tranby, Pamela A., author; Davies, Timothy Gray, advisor; Banning, James, committee member; Hall, Bruce, committee member; Kuk, Linda, committee member (Colorado State University. Libraries, 2012)
This phenomenological case study assesses the Riverland Community College faculty and staff current perceptions of organizational climate. It also examines the impact of the Academic Quality Improvement Program (AQIP) effort from 2002-2012. Employee perceptions were studied in two ways: (a) a longitudinal analysis (2002-2012) of an Institutional Climate Survey that was offered to all employees, and (b) personal interviews with seventeen of the employees: ten faculty and seven staff. Consistent interview questions were related to perceptions of current climate, discussions of related survey items from previous climate surveys (2002-2012), and perceptions of AQIP during the same ten-year period. Results from the qualitative and quantitative data analysis indicated radically different staff and faculty subclimates, as well as concerns related to organizational structure, administration, decision-making, communication, planning, and budget. Internal restructuring and reorganizations were problematic. AQIP efforts were not as relevant as concerns about climate and organizational structure, as AQIP does not seem have been influential in altering climate. The essence of the phenomenon for this case study was the bifurcated sense of climate at Riverland Community College. Two distinct subclimates were defined in this study: a toxic, fearful, and demoralizing environment experienced by some staff, including workplace bullying, and a non-threatening, supportive, and positive environment experienced by most faculty. There were many distinctive differences noted between the staff and faculty subclimates regarding climate perceptions, perspectives on organizational structure and its players, and AQIP.
Keywords: AQIP; subclimates; workplace bullying; organizational climate